2021
DOI: 10.1080/10942912.2021.1919702
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes of horse mackerel (Trachurus japonicus) during frozen storage as affected by double-glazing combined with theaflavins

Abstract: This study aims to investigate a new method of glazing for improving the storage quality of frozen horse mackerel. Specifically, this study explored the effect of double-glazing with theaflavins on the quality of horse mackerel stored at −20°C for 28 weeks by comparing with unglazed and those single glazed with theaflavins. Chemical indicators were used to assess deterioration during storage, the water-holding capacity (WHC), weight loss, drip loss, and low-field nuclear magnetic resonance (LF-NMR) were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The changes of FAAs in large yellow croaker on the fresh and different freezing treatments are presented in Table 2 . FAAs have a crucial role in the flavor development of aquatic products because they can give umami, sweetness, and bitterness, among other taste characteristics ( 67 ). Large yellow croaker had a low histidine level of <5 mg/100 g, which was in agreement with the findings of Wang et al ( 68 ) and Dou et al ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…The changes of FAAs in large yellow croaker on the fresh and different freezing treatments are presented in Table 2 . FAAs have a crucial role in the flavor development of aquatic products because they can give umami, sweetness, and bitterness, among other taste characteristics ( 67 ). Large yellow croaker had a low histidine level of <5 mg/100 g, which was in agreement with the findings of Wang et al ( 68 ) and Dou et al ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that the formation of sulfur volatiles increased in tilapia fillets with extended frozen storage time, which is further accompanied by an off-flavor of the fillets (X. Wang & Xie, 2021). The increased volatile flavor in mackerel during frozen storage could be associated with oxidation and denaturation of protein molecules and can also be related to freeze-induced lipid oxidation (Albertos et al, 2015).…”
Section: The Theory Of Lipid Oxidationmentioning
confidence: 96%
“…Thus, the appropriate glazing of seafood prior to the freezing period would protect the final product from dehydration, quality loss, and oxidation. Previous studies have shown the valuable effects of glazing by inhibiting lipid oxidation [ 6 , 7 ] and hydrolysis [ 8 , 9 ] development, volatile amine formation [ 10 , 11 ], and microbial activity [ 12 , 13 ]. Additionally, the glazing process has been shown to improve the pH value and water-holding capacity, colour, and textural properties of frozen fish [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%